2018
DOI: 10.1136/archdischild-2018-315412
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities for antibiotic stewardship among preterm infants

Abstract: Antibiotic stewardship programmes aim to optimise antimicrobial use to prevent the emergence of resistance species and protect patients from the side effects of unnecessary medication. The high incidence of systemic infection and associated mortality from these infections leads neonatal providers to frequently initiate antibiotic therapy and make empiric antibiotic courses one of the main contributors of antibiotic use in the neonatal units. Yet, premature infants are also at risk for acute life-threatening co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 67 publications
1
65
1
2
Order By: Relevance
“…41 In contrast to the aforementioned perception, antibiotic courses as brief as 4 days administered to very low and extremely low birth weight infants during the first week of life have been associated with a greater likelihood of adverse outcomes including chronic lung disease, necrotizing enterocolitis, invasive candidiasis and late-onset sepsis (possibly due to antibiotic-induced alterations in the neonatal intestinal microbiome). 36,37,42,43 Per Cantey and Patel, 35 "Neonatologists may be more receptive to implementing changes in their practice if advocated by a well-respected peer rather than ID doctors or pharmacists." Fortunately, increasing numbers of neonatologists are answering the call to advocate for neonatal AS.…”
Section: Hospitalistsmentioning
confidence: 99%
“…41 In contrast to the aforementioned perception, antibiotic courses as brief as 4 days administered to very low and extremely low birth weight infants during the first week of life have been associated with a greater likelihood of adverse outcomes including chronic lung disease, necrotizing enterocolitis, invasive candidiasis and late-onset sepsis (possibly due to antibiotic-induced alterations in the neonatal intestinal microbiome). 36,37,42,43 Per Cantey and Patel, 35 "Neonatologists may be more receptive to implementing changes in their practice if advocated by a well-respected peer rather than ID doctors or pharmacists." Fortunately, increasing numbers of neonatologists are answering the call to advocate for neonatal AS.…”
Section: Hospitalistsmentioning
confidence: 99%
“…A follow-up study by the same group showed a 22% decline in NICU antibiotic use from 2013 to 2016 (42,960 fewer antibiotic days) with a greater decline in NICUs with an established antibiotic stewardship program [125]. This and other studies suggest that further benefits may be gained by antibiotic stewardship [123].…”
Section: Attempts To Attenuate Neonatal Intestinal Dysbiosismentioning
confidence: 70%
“… 35 The choice of vancomycin is directed by concerns for methicillin-resistant Staphylococcus aureus (MRSA) infection, and the predominance of CoNS in the setting of LOS. 36 However, there are multiple studies showing that restricting empirical vancomycin use does not result in increased mortality or morbidity. 37 , 38 , 39 , 40 Chiu et al reported the effectiveness of implementing a restrictive vancomycin use guideline at 2 tertiary care centers.…”
Section: Antibiotic Use In the Neonatal Intensive Care Unit (Nicu)mentioning
confidence: 99%
“… 40 Thus, it is prudent to use an antistaphylococcal penicillin, such as oxacillin or nafcillin, along with an aminoglycoside for the initial empiric treatment of LOS. 7 , 36 , 38 , 39 , 40 , 41 , 42 , 43 Vancomycin should be considered judiciously in areas where MRSA is prevalent, or if the culture is positive for CoNS. 41 , 42 , 43 In the setting of a negative blood culture, with optimal collection technique, discontinuation of antibiotics should be considered.…”
Section: Antibiotic Use In the Neonatal Intensive Care Unit (Nicu)mentioning
confidence: 99%